Fungsi, Pendekatan, dan Bidang Garapan Pengelolaan Pendidikan Islam - Moh. Chairurrozikin; Haris Subahtiar (Jurnal Budi Pekerti Agama Islam, 2024)
In Islam, every action must be carried out carefully, correctly, orderly, and regularly, avoiding indiscriminate actions. The management of education in Islam must be done with precision and seriousness. Islamic education management is considered crucial in improving the quality of life of people who are experiencing underdevelopment, including moral, material, and spiritual aspects. This research method uses Library Research. In the context of" Educational Management, "the term" Islam " encourages intellectual responsibility to elaborate on the distinguishing attributes of Islamic Educational Management. Characteristics and characteristics of Islamic Education Management, which is based on Islamic values, includes the Qur'an and Hadith as a source of revelation that gives color to all aspects and activities. This makes the management of Islamic education as a means to improve the quality of life of people who are left behind. Thus, the management of Islamic education brings a positive impact in the development of the moral, material, and spiritual aspects of Muslims are discussed in detail.